STUDENTS' PERSPECTIVES ON THE USE OF DISCUSSION FORUM IN E-LEARNING TOWARDS CRITICAL THINKING SKILLS AT ONE UNIVERSITY IN JAMBI - Cemara Gita (Universitas Jambi, 2024)
The Discussion Forum is a feature of asynchronous learning in e-learning. It enables discussions between lecturers and students, as well as among students themselves. Unfortunately this feature is rarely used by lecturers while using e-learning. This research investigated students’ perspectives on the use of Discussion Forum in e-learning towards critical thinking skills. The aims of this research: (1) To describe students' experiences when using Discussion Forum in e-learning; (2) To describe students' perspectives on the use of Discussion Forum in e-learning, towards critical thinking skills. To collect the data for this research, qualitative methods such as interviews and document analysis were employed. The research was conducted at a university in Jambi, involving eight participants from the 2019 class of the English education study program. The findings of this research indicated that students are familiar with and have utilized Discussion Forum extensively during their e-learning journey. Notably, there are discernible signs of the application of critical thinking skills within this Discussion Forum. Almost all participants expressed their satisfaction with utilizing the Discussion Forum due to the absence of pressure and the opportunity to express their opinions without any sense of urgency. The participants affirmed that the use of Discussion Forum can be considered a valuable alternative for fostering critical thinking skills, particularly in an educational context. However, they also stated the need for significant guidance from lecturers and increased student participation to fully maximize the potential of the Discussion Forum. Keywords: Students’ perspectives; discussion forum; e-learning; critical thinking skills.